The Impact of Novelty and Meaningfulness Creative Marketing Program on Hotel Performance - Agustinus Widyartono, Antonius S. Setiawan, Lina, (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
At present, the hotel business is dealing with increasingly competitive competition. Creative marketing methods are developed to anticipate the competition. The implementation of creative marketing programs is a form of new strategies in the hotel industry. This study aims to prove the impact of the novelty and meaningfulness of creative marketing programs on hotel performance. The study is conducted with quantitative methods using primary data through a survey of owners/hotel general managers in Palembang city. A total of 75 questionnaires are distributed to the owners/hotel general managers. The number of questionnaires used in this study is 65 (87%). Structural Equation Modeling (SEM) Partial Least Squares (PLS) analysis using Warp PLS version 5.0 software is used to test of hypothesis. The results of the study indicate that the novelty and meaningfulness creative marketing program has a positive effect on the hotel's performance in Palembang city.